Analysis of Tool Design on a Slitter Machine Using AHOQ Method at PT XYZ - Helmy Ramadhani Putra Yongki; Risma Fitriani (OPSI, 2022)
PT. XYZ is a company that produces products according to orders from other companies, so the products produced vary greatly in terms of shape and size. Of the many variations of products produced, all products made must go through the process of cutting raw materials using a slitter machine. In this cutting process, workers have various complaints and problems in operating the slitter machine. Therefore, it is necessary to analyze the design of tools using the integration model between AD and HOQ or often called the Axiomatic House of Quality (AHOQ). This research was conducted using the AHOQ method with observation, interviews, and data analysis techniques. From the AHOQ that has been obtained, there are 3 kinds of alternative combinations of design concepts. The combination of alternatives that have been obtained is carried out with a design concept using the scoring method. Based on the assessment method, the concept chosen is a combination of alternative 3 with a total weighted value of 2.9. From the final product design, suggestions are given, namely the material used in the design concept must be durable and the grip material in the design concept must use comfortable materials.